2016
DOI: 10.1002/adsc.201600169
|View full text |Cite
|
Sign up to set email alerts
|

Potassium tert‐Butoxide‐Promoted Synthesis of 1‐Aminoisoquinolines from 2‐Methylbenzonitriles and Benzonitriles under Catalyst‐Free Conditions

Abstract: Herein a practical and efficient protocol for preparing a range of aminoisoquinolines is reported. Various aminoisoquinolines were prepared in moderate to good yields from the corresponding 2‐methylbenzonitriles and benzonitriles upon treatment with potassium tert‐butoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The reactions conditions shows good applicability to wide range of substrates in synthesizing 1-aminoisoquinolines (Scheme 287). [287] According to the proposed mechanism, the reaction is expected to begin with KOtBu mediated proton abstraction Gutiérrez group have reported heterocyclization that involves α-benzyl TosMIC derivatives 471 and different electrophiles 472 towards the synthesis of 1substituted isoquinolines 473 (Scheme 289). [288] Salfeena et al reported BF 3 -etherate mediated onepot synthesis of 5,6-dihydroisoquinoline derivatives 475 from readily available α,β-unsaturated ketones/ arylidene ketones 474, substituted nitriles 449 and aryl acetylenes 114.…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…The reactions conditions shows good applicability to wide range of substrates in synthesizing 1-aminoisoquinolines (Scheme 287). [287] According to the proposed mechanism, the reaction is expected to begin with KOtBu mediated proton abstraction Gutiérrez group have reported heterocyclization that involves α-benzyl TosMIC derivatives 471 and different electrophiles 472 towards the synthesis of 1substituted isoquinolines 473 (Scheme 289). [288] Salfeena et al reported BF 3 -etherate mediated onepot synthesis of 5,6-dihydroisoquinoline derivatives 475 from readily available α,β-unsaturated ketones/ arylidene ketones 474, substituted nitriles 449 and aryl acetylenes 114.…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…Quinoline and quinazolinones molecules (Table 1, 2) were synthesized during the original synthetic methodologies studies (Shen et al ., 2015, 2016; Feng and Wu, 2016). The purity of each compound was greater 99% and confirmed by gas chromatography-mass spectrometry and nuclear magnetic resonance (1H-NMR and 13C-NMR).…”
Section: Methodsmentioning
confidence: 99%
“…Wu and Feng disclosed a novel procedure toward 1‐aminoisoquinolines via the reaction of o ‐toluenenitriles and benzonitriles upon treatment with potassium tert ‐butoxide. However, these approaches were difficult to construct multisubstituted 1‐aminoisoquinolines . Recently, our group has been devoted to the construction of 4 H ‐pyran/1,4‐dihydropyridine‐based solid‐state fluorescence stimulus‐responsive materials using 2,6‐dimethyl‐4‐pyrone ( 1 ) as the starting material (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%